Human nature, transhumanism and digital transformation - Yu. Vorontsova; E. Postigo Solana (E-Management, 2019)
The limits of misunderstanding associated with the implementation of the radical transhumanist project of transforming human nature into a posthuman being through the development and implementation of biotechnology have been presented briefly. Human intelligence has prejudices and assertions, that are physical, but these obstacles must be considered in the context of history and culture, which in turn are independent of physical limitations. The issues, related to the digital transformation of society, through the introduction of new technologies, as the implementation stage of the concept of transhumanism, also have been considered in the article. The problems of the moral dimension of human activity, related to the intervention of the digitalization process in it, have been considered. Prudential reflection, precaution, respect for the integrity and lives of people, their dignity and freedom, justice and the common welfare should form the responsibility to future generations for all kinds of technological interventions. The authors have proposed a conception, based on an interdisciplinary approach, which allows us to interconnect different areas of knowledge in the field of bioethics, economics, philosophy, etc. in order to identify and assess the risks behind the use of technological innovations (digital transformation), in the implementation of the philosophy of transhumanism. The use of ethical postulates will create a structure in which management decisions envisage technological innovations based on their utility for benefits on the one hand and the well-being of people on the other hand.